Â¬Â¬PERANCANGAN BUKU POP-UP RANGKAIAN HARI RAYA NYEPI SEBAGAI MEDIA PEMBELAJARAN SISWA HINDU DI SEKOLAH DASAR - Yasa, I Nyoman Miyarta (Institut Hindu Dharma Negeri Denpasar, 2021)
Hinduism has so many rituals or ceremonies to celebrate. One of them is a ceremony to commemorate the Saka New Year which in Indonesia is known as Nyepi Day. Nyepi, Hindus are a series of holidays starting from a few days before and after the holidays, this series of holidays should be introduced, studied, and understood, especially for children of primary school age, because later the children are which will be the successor to the preservation of rituals and knowledge of religion. So there is a need for media that attracts children's interest in studying the framework of Nyepi. So the aim of this research is to design learning aids in the form of a pop-up book that discusses the series of Nyepi holidays which are simple but can be interesting so that they are easily understood by children. This design uses the Design Thinking method to get the right problem-solving solution in designing the work. There are two media in the design, namely the primary media for the book Pop-Up Series Hari Raya Nyepi and secondary media, namely X-Banner and merchandise. By designing the Pop-Up book for the Nyepi holiday series, it is hoped that it can become a new media choice as a learning companion in order to experience the series of Nyepi holidays for children at the elementary school level.